PENGARUH KEGIATAN BERMAIN CLAY BERBASIS PROYEK TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA MUARA TEMBESI - Friska septiardilla; Sri Indriani Harianja; Akhmad Fikri Rosyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is based on the results of field research observations that show that children's fine motor skills have not developed optimally. This study aims to determine the effect of project-based Clay play activities on the fine motor skills of children aged 4-5 years at TK Pembina Muara Tembesi. This study uses a preexperimental designs method. The sampling technique used purposive sampling. Data collection involved pre-test and post-test, and hypothesis testing was carried out using the t-test on normally distributed data. The results showed that Clay play activities significantly improved children's fine motor skills, as shown by the results of the t-test t count (24.617)> t table (2.160). With the Cohen's formula, there is a value of 3.78 which is in the range> 1 with a strong interpretation (Strong Effect). In conclusion, there is an effect of project-based Clay play activities on the fine motor skills of children aged 4-5 years at TK Negeri Pembina Muara Tembesi.